Peer-to-Peer Energy Trading of a Community Connected with an AC and DC Microgrid - Kuruseelan S; Vaithilingam C (Energies, 2019)
The awareness of self-consumption of grid-connected roof-top solar photovoltaic (PV) owners in a community and the advancement in information and communication technologies (ICT) led to the development of a novel peer-to-peer energy trading mechanism for next-generation power systems. In the peer-to-peer (P2P) energy trading landscape, the prosumers and consumers self-organize and trade energy among themselves. In recent years, the large penetration of distributed energy resources, as well as the advancement of technologies in the fields of protection, power electronics, and storage devices, led to the use of direct current (DC) home appliances by the end-users, i.e., consumers in a community. In this paper, the operational costs of an individual household and community when operated with alternating current (AC) and DC home appliances are calculated using bill sharing and the mid-market rate method for various degrees of PV penetration. The bill sharing method shares the operational cost and income among all the peers in proportion to the amount of energy they consume/generate. The mid-market rate method calculates the P2P internal price at the median of the import and export price based on the relationship between total generation and demand. In terms of operational cost, both producers and consumers benefit fairly when the mid-market rate method is used when the households in a community are operated with DC home appliances.